Association of Plasma Homocysteine, Serum Folic Acid and Vitamin B12 Concentrations and MTHFR C677T Polymorphism with Preeclampsia - Işık Üstüner; Murat Sönmezer; Bora Cengiz; Halil Gürhan Karabulut; Atilla Halil Elhan; Feride Söylemez (Medical Network, 2006)
OBJECTIVE: This study aims to ev aluate the association between preeclampsia and plasma homocysteine, serum folic acid, v itamin B12 concentrations and MTHFR C677T polymorphism. STUDY DESIGN: This study was a case-control study including 20 pregnant females with preeclampsia and 30 healthy normotensive pregnant (ages 18-40) females. Plasma homocysteine, serum folic acid and vitamin B12 concentrations were measured in all patients in the third trimester of pregnancy and MTHFR C677T polymorphism was also analyzed. RESULTS: The risk of preeclampsia in patients with homocysteine concentrations >8.65 μmol/L increased 8-f old as compared to homocysteine concentrations <6.19 μmol/L. While the mean plasma homocysteine concentration (8.65±2.05 μmol/L vs. 6.19±1.52 μmol/L, p<0.001), was high in the preeclampsia group as compared to controls, the mean serum folic acid concentration was signif icantly low (11.49±8.96 ng/ml vs. 15.15±6.7 ng/ml, p= 0.020). No significant difference was noted between the groups regarding mean serum vitamin B12 concentrations (241.1±111.7 pg/ml vs. 236±111.1 pg/ml, p=0.879) and MTHFR C677T polymorphism including MTHFR gene TT/CT/CC genoty pes. CONCLUSION: Elevated third trimester plasma homocysteine concentrations were associated with increased risk of preeclampsia. This association was more pronounced in our study which may also be related to synergistic effect of the coexistent folic acid deficiency. MTHFR C677T polymorphism could not alone explain the hyperhomocysteinemia in patients with preeclampsia